The pharmacodynamic equivalence of Orlistat 60 mg capsule. An open label, balanced, randomized, multiple-dose, cross-over pharmacodynamic end-point bioequivalence study in healthy, adult, human Asian Indian subjects under fed conditions. (4th November 2013) - Kumar, Sudershan; Monif, Tausif; Arora, Rachna; Khuroo, Arshad; Jain, Rakesh; Reyar, Simrit; Verma, Priya Ranjan Prasad; Rao, Shireen
Abstract: Orlistat is a non-systemic treatment for obesity. The drug inhibits lipase in the gastrointestinal track mainly in the lumen of the stomach and small intestine by binding reversibly with the active site of gastric and pancreatic lipases, preventing the absorption of ∼30–35% of dietary fat. The undigested triglycerides are not absorbed, resulting in a caloric deficit and positive effect in weight control. The objective of this study was to assess the bioequivalence of orlistat administered as a generic and reference capsule formulations using a pharmacodynamic end-point. A total of 60 healthy volunteers followed a 5-day run-in diet period to be accustomed to a low fat diet; subjects were then randomized to receive under fed conditions oral doses of orlistat (60 mg) 3-times daily for 10 days as the generic (Ranbaxy Laboratories) or reference (Alli™, GlaxoSmithKline) capsule formulations. Subjects followed a standardized diet (2500 kcal/day, ∼30% as fat) for the entire study. Feces were collected over the last 2 days of the run-in period (baseline) and over the last 5 days of the two treatment periods. The amount of fat in meals and feces were assayed using the validated FTIR method with a limit of detection of 1.00 g%, respectively. Fecal fat excretion over 24 h (FFE24SS, calculated as the amount of fat excreted in feces adjusted by the amount of fat ingested) was used as a pharmacodynamic end-point to assess the bioequivalence between the two orlistat formulations. An analyses of variance (ANOVA) was performed on the log-transformed FFE24SS parameter to establish bioequivalence of the generic product with respect to the innovator formulation. Mean FFE24SS values at baseline and after repeated oral administrations of the generic and innovator formulations of orlistat were 0.88%, 40.55% and 40.54%, respectively. The ratio of least-squares means (LSM) of FFE24SS of the generic to the innovator formulation was 101.90%, with 90% confidence intervals of 97.94–106.01%. Orlistat was well tolerated by subjects in both periods of study and no serious adverse events were observed during the study. In conclusion, mean FFE24SS values were used as pharmacodynamic end-points to assess bioequivalence between two formulations of orlistat. Results from this study suggest that the test formulation of Orlistat capsule is bioequivalent to the reference marketed Alli™ when administered to healthy volunteers as a multiple dose under fed conditions.